2017
DOI: 10.14254/2071-8330.2017/10-3/19
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the power of renewable energy sources in the context of classical electricity system transformation

Abstract: Abstract. Many regions, not only in the Europe, introduce plans for the modernization of energy systems so that in a few or several years most of the demand for electricity was being able to cover using renewable energy sources. The aim of this paper is to present the possibility of estimation of appropriate power supply based on the renewable energy sources in the context of the whole energy system in the annual balance, taking into account the technical and the economic optimization strategies. The article p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…The promotion of renewable energy power generation is conducive to emission reduction and environmental protection, and is an important way to achieve low-carbon energy transformation [2]. Many countries have already developed plans to use renewable energy to generate electricity for the large-scale utilization of renewable resources in the next few years [3]. However, due to the high cost and instability of renewable energy power generation, it is less competitive than traditional fossil energy power generation [4,5].…”
Section: Research Backgroundmentioning
confidence: 99%
“…The promotion of renewable energy power generation is conducive to emission reduction and environmental protection, and is an important way to achieve low-carbon energy transformation [2]. Many countries have already developed plans to use renewable energy to generate electricity for the large-scale utilization of renewable resources in the next few years [3]. However, due to the high cost and instability of renewable energy power generation, it is less competitive than traditional fossil energy power generation [4,5].…”
Section: Research Backgroundmentioning
confidence: 99%
“…This solution offers higher reliability of supply in most remote areas. Nowadays, renewable-based mini-grids relying on local resources have the potential of further minimizing import resource dependencies [123]. In addition, their local environmental impact can be small [124].…”
Section: Ensuring Reliability Of Supply and Environmental Securitymentioning
confidence: 99%
“…Furthermore, the effect of energy efficient practices on the techno-economic and environmental features of HRES have not been comprehensively investigated (see Table 1). Apart from these, it has also been reported that many HRES were not able to adequately address the challenges faced by energy consumers especially in the Global South, in the past because the choice of these HRES alternatives were solely based on a single criterion: either the technical or economic [37][38][39]. As such, the selection and ranking of HRES alternatives based on multiple criteria have not been comprehensively considered in household applications.…”
Section: Reference Technical Economic Emission Energy Efficiency Mcdmmentioning
confidence: 99%